The technological feasibility of the installation of a production plant for a drink from carob (prosopis pallida), tarwi (lupinus mutabilis), and quinoa (chenopodium quinoa) - Manrique Pasión, Maggie Lalesca (2021)
This article aims to expose the technological viability of a plant that produces a carob, tarwi, and quinoa drink through the definition of the product, the production process, and the plant capacity. This drink is an alternative to a large number of juices and sodas that have high sugar content. In addition, since it is made from a mixture of two legumes and a pseudo-cereal, it provides essential amino acids to the human body.